Transformations in identity, governance and planning: The case of the small city. (May 2016) - James, Katie; Thompson-Fawcett, Michelle; Hansen, Carsten Jahn
Cities that have transformed in response to socio-economic crises are a focus of theorists interested in identifying why changes are triggered and how they are played out. Stories of success add to knowledge of 'fruitful' city functioning. This paper examines how transformations in urban governance and planning can unfold in smaller cities by scrutinising the New Zealand city of Invercargill. The city underwent metamorphosis from a faded town with a negative image to one that has a new path despite isolation and small population. Leadership, networking and innovation have been key factors. The paper unveils how development fortunes on the global periphery can be reshaped by strong place leadership, revised connections between different tiers of policy making, and reframed processes of governance and planning.